2018
DOI: 10.1016/j.ijpara.2017.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and toxin family analysis of the paralysis tick, Ixodes holocyclus

Abstract: The Australian paralysis tick (Ixodes holocyclus) secretes neuropathic toxins into saliva that induce host paralysis. Salivary glands and viscera were dissected from fully engorged female I. holocyclus ticks collected from dogs and cats with paralysis symptoms. cDNA from both tissue samples were sequenced using Illumina HiSeq 100 bp pair end read technologies. Unique and nonredundant holocyclotoxin (HT) sequences were designated as HT2 to HT19, as none were identical to the previously described HT1. Specific b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 67 publications
1
41
0
Order By: Relevance
“…Similarly, chymotrypsin was highly upregulated in soldier fly salivary glands in response to feeding on sugarcane roots (Log 2 FC > 7). Chymotrypsin is a serine protease enzyme involved in many different pathways, especially in blood‐sucking insects [e.g., mosquitoes, assassin bugs ( Triatoma ) and the paralysis tick, Ixodes holocyclus ] (Rodriguez‐Valle et al ., ) where they degrade elastin and other components in extracellular matrix during feeding. Insect herbivores chymotrypsins can possibly be used to cleave internal peptide bonds in plant proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, chymotrypsin was highly upregulated in soldier fly salivary glands in response to feeding on sugarcane roots (Log 2 FC > 7). Chymotrypsin is a serine protease enzyme involved in many different pathways, especially in blood‐sucking insects [e.g., mosquitoes, assassin bugs ( Triatoma ) and the paralysis tick, Ixodes holocyclus ] (Rodriguez‐Valle et al ., ) where they degrade elastin and other components in extracellular matrix during feeding. Insect herbivores chymotrypsins can possibly be used to cleave internal peptide bonds in plant proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Motobu et al (2007) identified an H. longicornis SCP predominantly expressed in tick midgut upregulated in response to blood feeding, which has been described to play a role in hemoglobin degradation. SCPs were highly expressed in salivary glands and viscera from fully engorged Ixodes holocyclus female ticks (Rodriguez-Valle et al, 2018). The secretory/excretory proteome of helminths parasites identified SCPs that are part of a protein complex that regulates parasite-host interaction (Morassutti et al, 2012).…”
Section: Degs Between Ticks Fed On Tick-susceptible and Resistant Cattlementioning
confidence: 99%
“…Again, in this second attempt at a vaccine using recombinant protein production methods, no product was commercialised . A third generation of a tick paralysis vaccine was recently reported using synthetic peptides based on expressed protein sequences found in late‐stage engorged ticks but only limited protective efficacy has been demonstrated to date . Vaccine development has always been competing against other preventative methods and the recent commercialisation of various isoxazoline compounds, their low cost and convenient dosing formulations makes it difficult to see an injectable vaccine ever be competitive.…”
Section: Preventatives That Workmentioning
confidence: 99%
“…A recombinant version of Holocyclotoxin 1 was successfully produced in yeast and published in 2017 but no mouse studies were described to support lethal in vivo biological activity . In another study published by the same group in 2018, a range of Holocyclotoxin peptides were synthesised based on patented sequences, injected into neonatal mice and paralytic effects were observed . The conclusions that can be reached based on all the studies to date are that the paralysis tick likely produces a swathe of peptides that may act synergistically or in varying proportions to induce paralysis of the host.…”
Section: Modern Molecular Parasitology Uncovers Enigmatic Tick Toxinmentioning
confidence: 99%